INTERPOLATION LOGISTIC FUNCTION IN THE SURFACE POTENTIAL BASED MOSFET MODELING - Kevkić, Tijana; Stojanović, Vladica (Bulletin of Natural Sciences Research, 2018)
Introduction of the Interpolation Logistic (IL) function in an approximate Surface-Potential-Based MOSFET model has been proposed in this paper. This function can be precisely determined in accordance with different MOSFET device characteristics. The IL function also provides continual behavior of the surface potential in entire useful region of MOSFET operation. Unlike the approximate analytical models which can meet in literature, continual and smooth transition of the surface potential between weak and strong inversion region here is achieved without using of any empirical parameter. Furthermore, thanks to the IL function, speed and manner of that transition are controlled. The values obtained for the surface potential are verified extensively with the numerical data, and a great agreement is found for the MOSFET devices from different technology generations.
Keywords: MOSFET modeling; Interpolation Logistic function; Surface potential; Parameters estimation